Mercado de música gospel : como nasce uma indústria cultural - Costa, Edson Ramos de Oliveira Costa (2017)
The research has as main problem to understand what characterizes, and how works in Brazil the process of generating value, in the market of evangelical cultural products, commonly called gospel. The cropped field is the Brazilian recorded music market and its ramifications, the object is the production chain of the music, analyzed through the work of artists, managers of Record Company, music streaming company and physical store of discs. The theoretical reference adopted is the Political Economy of Communication, through two central concepts: Cultural Industry and mediation. The expository method adopted is historical / dialectical materialism, through which one intends to think of the gospel market as a complex phenomenon, formed by the relation between the social and economic macrostructures and the historical and cultural particularities of a segment. The starting hypothesis is that the term gospel discriminates the evangelical music of the others in function of responding to a characteristic of the Brazilian evangelical culture; however, this does not hurt the generation of value in the production chain of music, nor does it prevent this segmented market from becoming another manifestation of the mediation role played by the cultural industry. The techniques used were bibliographical and documentary analysis, structured and semistructured interview with artist and managers, and the biographical method, through the narrative of the careers of some artists not interviewed. The hypothesis was confirmed, and more: the differentiation that the term gospel brings back does not depend on the music or the audience, but on the artist, and the other managers, and the faith they profess. Thus, the particularities of gospel music are also appropriate to the emergence of a cultural industry.